PEDAGOGUE(S) OF CHILDREN AND CRITICAL THINKERS OF EDUCATION - Euclides Redin (Editora da Universidade de Santa Cruz do Sul, 2009)
The rediscovery of the infancy of Pedagogy passes through the redefinitions of the roles of the Pedagogue. The search for the origin of this role leads to outlining the position of child conduction in times when childhood is set as a requirement of citizenship and of public policies of guarantee to children's rights in a new project of Nation. Originally the pedagogue was the slave who conducted the child of the master. Nowadays the role of the pedagogue as conductor remains; however, of the infant citizen: both as protagonists of an emancipatory project of citizenship. New doings, new agents, new legal challenges, new fights for the cause of always: childhood inequality. Keywords: pedagogy(ies), childhood, public policies, pedagogue profession